2022
DOI: 10.3389/fonc.2022.877617
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of RECQL Protein in ER-Positive Breast Tumours Is Associated With a Better Survival

Abstract: BackgroundRECQL (also known as RECQ1 and RECQL1) is a gene of recent interest in breast cancer and an association between high levels of RECQL protein in breast cancer tumour cells and good survival of patients has been reported.MethodsTo validate this association, we measured the RECQL protein levels in tumours of 933 breast cancer patients using immunohistochemistry analysis and followed the patients for death from breast cancer.ResultsWomen with a level of RECQL protein above the 75th percentile had better … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…In sporadic invasive breast cancers (IBC), we demonstrated that RECQL deficiency at the transcriptomic and proteomic levels are associated with aggressive breast cancer phenotypes and poor patient survival [6] . More recently, we validated these observations in an independent clinical cohort of ER-positive breast cancer where RECQL deficiency was associated with poor survival [7] . Pre-clinically, in ER-positive breast cancer cells, we observed that RECQL interacts with the FOXA1 transcription factor and regulates expression of the ESR1 gene which encodes the ERα protein [8] .…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…In sporadic invasive breast cancers (IBC), we demonstrated that RECQL deficiency at the transcriptomic and proteomic levels are associated with aggressive breast cancer phenotypes and poor patient survival [6] . More recently, we validated these observations in an independent clinical cohort of ER-positive breast cancer where RECQL deficiency was associated with poor survival [7] . Pre-clinically, in ER-positive breast cancer cells, we observed that RECQL interacts with the FOXA1 transcription factor and regulates expression of the ESR1 gene which encodes the ERα protein [8] .…”
Section: Introductionsupporting
confidence: 56%
“…We have previously shown that low levels of RECQL protein is associated with aggressive IBC including larger tumor size, lymph node positivity, high tumor grade, high mitotic index, pleomorphism, dedifferentiation, ER negativity and poor survival [ 6 , 7 ]. We hypothesized that RECQL deficiency induced genomic instability [ 3 , 4 ] will not only lead to increased mutagenicity/carcinogenicity but can also increase neoantigen load on tumor cell surface resulting in increased immunogenicity and T-cell infiltration [9] .…”
Section: Resultsmentioning
confidence: 99%
“…Earlier investigations indicated that increased RECQL1 expression was associated with poorer OS and PFI in patients with LGG [ 14 ]. On the other hand, ER-positive breast cancer patients who had a RECQL protein level above the 75th percentile experienced improved DSS over a 15-year period, particularly among women [ 60 ]. Increased expression of BLM is associated with decreased OS in bladder cancer and reduced DFI in cholangiocarcinoma [ 13 , 61 ].…”
Section: Discussionmentioning
confidence: 99%